2019
DOI: 10.1002/jor.24520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Conditions and Activation on Growth Factor Concentration in Platelet‐Rich Plasma

Abstract: This study aimed to evaluate growth factor concentration in platelet‐rich plasma (PRP) (leukocyte‐rich PRP) based on storage temperature, duration of storage, and method of activation. PRP samples were stored at 24℃ (room temperature group), 4℃ (refrigerator group), and −70℃ (deep‐freezer group). In each temperature, four aliquots were prepared based on the time of analysis (immediately, 1, 3, and 7 days after preparation). After storage, concentrations of platelet‐derived growth factor‐AA (PDGF‐AA), transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…FGF has a role in mitogenesis, differentiation, angiogenesis, cellular migration, and also wound healing. Recently, the effects of storage conditions on GF release of human PRP have been studied [ 63 , 64 , 65 ]. All these works have highlighted the importance of the storage time and temperature on GFs release from PRP and how these parameters can be controlled to modulate its biological properties.…”
Section: Resultsmentioning
confidence: 99%
“…FGF has a role in mitogenesis, differentiation, angiogenesis, cellular migration, and also wound healing. Recently, the effects of storage conditions on GF release of human PRP have been studied [ 63 , 64 , 65 ]. All these works have highlighted the importance of the storage time and temperature on GFs release from PRP and how these parameters can be controlled to modulate its biological properties.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the plasma was preserved and frozen at −80 • C until the determination of GF concentrations. According to previous studies, storing platelet-rich plasma at −80 • C does not cause significant changes in platelet count, growth factors' concentration, the content of 5-HT, and inflammatory effects [75][76][77] (Figure 7).…”
Section: Methodsmentioning
confidence: 60%
“…Furthermore, it addresses other challenges with plasma use, such as storage, transport, batch variability, and availability. The freeze-dried PPP and PRP powders can be stored for up to 2 years at room temperature without significant loss in bioactivity [5,13,[27][28][29]. It was also observed that the pH of the reconstituted solution increased to 8.6 ± 0.31 (n = 12) for both PPP and PRP fractions.…”
Section: Processing Raw Materialsmentioning
confidence: 94%